2007
DOI: 10.1073/pnas.0700229104
|View full text |Cite
|
Sign up to set email alerts
|

Reburn severity in managed and unmanaged vegetation in a large wildfire

Abstract: Debate over the influence of postwildfire management on future fire severity is occurring in the absence of empirical studies. We used satellite data, government agency records, and aerial photography to examine a forest landscape in southwest Oregon that burned in 1987 and then was subject, in part, to salvage-logging and conifer planting before it reburned during the 2002 Biscuit Fire. Areas that burned severely in 1987 tended to reburn at high severity in 2002, after controlling for the influence of several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
241
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(260 citation statements)
references
References 29 publications
14
241
1
Order By: Relevance
“…16-day temporal resolution, and a deep catalogue of publicly-available images dating back to 1984. Landsat images and burn severity maps derived from them have been invaluable for developing an atlas of burn severity for large fires in the US [1], determining the drivers of burn severity [2][3][4], measuring the effect of past disturbance and management on burn severity [5][6][7], and quantifying the effects of fire on biotic communities [8].…”
Section: Introductionmentioning
confidence: 99%
“…16-day temporal resolution, and a deep catalogue of publicly-available images dating back to 1984. Landsat images and burn severity maps derived from them have been invaluable for developing an atlas of burn severity for large fires in the US [1], determining the drivers of burn severity [2][3][4], measuring the effect of past disturbance and management on burn severity [5][6][7], and quantifying the effects of fire on biotic communities [8].…”
Section: Introductionmentioning
confidence: 99%
“…Spyratos et al (2007) modeled the expansion of fire at the wildland-urban interface by considering the flammability of houses. Thompson et al (2007) discussed the impact of post-wildfire management on future fire severity and concluded that areas that were salvage-logged and planted after the initial fire burned more severely than comparable unmanaged areas, suggesting that fuel conditions in conifer plantations can increase fire severity despite the removal of large woody fuels.…”
Section: Forestrymentioning
confidence: 99%
“…Conversely, logging can make moist or wet forests more fire prone [17]. Indeed, clear evidence of such inter-relationships can be found in tropical rainforests [7,8], wet temperate forests in western North America [9], and wet temperate forests in Australia [18••, 19, 20], although some moist forests may be an exception to this general response [21].…”
Section: Logging and Fire Interactionsmentioning
confidence: 99%
“…Logging may alter landscape structure not only as a result of cutting patterns but also indirectly through interactions with other kinds of disturbances such as fire regimes [7][8][9]. In this report, I provide some perspectives on relationships between forest landscape structure and natural resource management, with a particular focus on the effects of logging in wet forests where fire regimes (sensu [10,11]) are typically rare, highseverity stand-replacing conflagrations.…”
Section: Introductionmentioning
confidence: 99%